Guaiazulene derivative 1, 2, 3, 4‐tetrahydroazuleno[1, 2‐b] tropone reduces the production of ATP by inhibiting electron transfer complex II. Issue 11 (21st September 2021) - Kasami, Chieko; Yamaguchi, Jun‐ichi; Inoue, Hideki
Abstract : Molecularly targeted therapy has been used for treatment of various types of cancer. However, cancer cells often acquire resistance to molecularly targeted drugs that inhibit specific molecular abnormalities, such as constitutive activation of kinases. Even in cancer cells that have acquired resistance, enhanced anabolism, including the synthesis of nucleotides, amino acids and lipids, is common to normal cancer cells. Therefore, there is a renewed interest in effectively eliminating cancer cells by specifically targeting their abnormal energy metabolism. Multiple strategies are currently being developed for mitochondrial‐targeted cancer therapy, with agents targeting oxidative phosphorylation, glycolysis, the tricarboxylic acid cycle and apoptosis. In this study, we found that one of the guaiazulene derivatives, namely, 1, 2, 3, 4‐tetrahydroazuleno[1, 2‐ b ] tropone (TAT), inhibited the proliferation of cancer cell lines stronger than that of normal cells. In addition, we showed that TAT inhibited energy production in cancer cell lines, resulting in apoptosis. Analyses done in cancer cell lines and in the animal model Caenorhabditis elegans suggested that TAT acts on the mitochondrial electron transfer complex II and suppresses cellular energy production by inhibiting oxidative phosphorylation across species. These results suggest that TAT could represent a novel anticancer agent that selectively targets mitochondria. Abstract : Here we demonstrate that a guaiazulene derivative, namely, 1, 2, 3, 4‐tetrahydroazuleno[1, 2‐ b ] tropone (TAT), inhibits the proliferation of cancer cell lines. TAT acts on mitochondrial electron transfer complex II by inhibiting oxidative phosphorylation, thereby suppressing cellular ATP production, which leads to cellular energy deprivation and cell death. These results suggest that TAT has the potential to be a novel anticancer agent that selectively targets mitochondria.